Literaturnyi al'manakh . Literaturnyi al'manakh . Literary Almanac . Литературный альманах - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Discussion of the ideological and artistic originality of the novel by Chingiz Aitmatov, "Plaha"; opening of the Khlebnikov museum; an interview with the writer Andrei Bitov; discussion of the multiple uses of advertising in U.S. media. Featured in the program: Lakshin, Vladimir IAkovlevich (Literary Expert); Anninskii, Lev Aleksandrovich (Literary Expert); Zolotusskii, Igor' (Literary Expert); Khlebnikov, Velimir (Poet); Triapkin, Nikolai (Poet); Mel'vil', Andrei IUr'evich (Department Head of the Institute of USA and Canada); Nikitin, Aleksandr (Senior Researcher at the Institute of the USA and Canada); Bitov, Andrei Georgievich (Writer) Обсуждение идейно-художественного своеобразия романа Чингиза Айтматова ’Плаха’; открытие музея Хлебникова; интервью с писателем Андреем Битовым; обсуждение мультифункционального использования рекламы в Американском СМИ. В программе участвуют: Лакшин, Владимир Яковлевич (Литературовед); Аннинский, Лев Александрович (Литературовед); Золотусский, Игорь (Литературовед); Хлебников, Велимир (Поэт); Тряпкин, Николай (Поэт); Мельвиль, Андрей Юрьевич (Заведующий сектором Института США и Канады); Никитин, Александр (Старший научный сотрудник Института США и Канады); Битов, Андрей Георгиевич (Писатель)